Transformation of patchouli alcohol to β-patchoulene by gastric juice: β-patchoulene is more effective in preventing ethanol-induced gastric injury - Yuhong Liu (Nature Portfolio, 2017)
Abstract Pogostemonis Herba is a functional food approved in Asian countries. Its major constituent, patchouli alcohol (PA), possesses a gastroprotective effect and is reported to transform into β-patchoulene (β-PAE) under acidic conditions. To investigate whether β-PAE, the metabolite of PA, has a protective effect on the gastrointestinal tract, the formation of β-PAE by gastric juice and the anti-ulcerogenic potential of β-PAE against ethanol-induced gastric injury were evaluated. The Results indicated that PA was converted to β-PAE by rat gastric juice. Additionally, β-PAE was significantly better than PA at reducing the area of gastric ulcer. The overproduction of malondialdehyde, tumour necrosis factor-α, interleukin (IL)-1β, IL-6, Fas, FasL and caspase-3 was markedly inhibited by β-PAE while the underproduction of superoxide dismutase, glutathione and catalase was significantly improved. β-PAE also regulated the NF-κB and ERK1/2 signalling pathways. Our findings suggest that β-PAE has potential therapeutic efficacy for antiulcer treatment.